The Impact of Entertainment, Interactivity, Trendiness, Customization, and EWOM on Consumer’s Willingness to Pay a Premium Price for Samsung Smartphones : Mediating Effects of Brand Awareness, Image, and Loyalty through Instagram - Axel Nathan Gabriello; Sabrina O. Sihombing (Universitas Pelita Harapan, 2024)
In this research, this study investigates the effect between SMMA and the willingness to pay a premium price for Samsung smartphones. With an emphasis on the mediating functions of brand awareness, brand image, and also brand loyalty. It particularly examines how these activities affect consumer behavior. Data was collected through a survey of 288 participants who own Samsung smartphones and are frequent Instagram users, using a quantitative methodology. To investigate further the use of structural equation modeling (SEM) was employed. The study show that brand awareness and brand image act as mediators between SMMA, brand loyalty, and willingness to pay a premium price. According to these results, social media content that is both personalized and engaging can improve brand perception, which in turn would cause to a rise in customer loyalty and a higher willingness to pay for high-end goods. This study gives marketers valuable information about on how to make use of social media activities in acts to improve pricing and brand value.